(untitled) (المجلة الدولية للبحوث العلمية, 2026)
The problem of this study lies in the limited accuracy of meteorological station data in representing the spatial variability of rainfall in Wadi Al-Huski basin, which affects the estimation of surface runoff and flood risk assessment. The study aims to analyze the hydrological behavior of the basin and estimate surface runoff using the SCS-CN model supported by GIS techniques.The study adopts a quantitative and applied approach using climatic data and satellite imagery, due to their effectiveness in analyzing natural characteristics and simulating surface runoff. The results indicate an increase in future surface runoff despite the slight rise in rainfall, with clear spatial variability and concentration along drainage channels. Most of the basin falls under low to moderate flood risk levels, with limited high-risk areas. The study recommends developing early warning systems, avoiding urban expansion in high-risk areas, and enhancing the use of spatial technologies in flood management.